Frequency Dependence of Electroluminescence Measurement in LDPE - Nurul Aini Bani; Zulkurnain Abdul-Malek; Siti Armiza Mohd Aris; Siti Zura A. Jalil; Mohd Nabil Muhtazaruddin; Hazilah Mad Kaidi; Sharipah Alwiah Syed Abd Rahman; Firdaus Muhammad-Sukki; Abdullahi Abubakar Mas’ud; Siti Hawa Abu-Bakar; Jorge Alfredo Ardilla Rey (International Journal of Electrical and Computer Engineering (IJECE), 2017)
A good insulator for high voltage cable has low dielectric loss, reasonable flexibility and thermo-mechanically stable. However, prolonged application of electrical stresses on the cable will degraded the cable; physically and morphologically. Electrical degradation in high voltage cable can be detected using electroluminescence (EL) method. Electroluminescence is a phenomenon that occurs when the atoms of a material are being excited due to the application of and external high electrical stresses. There are several external factors that affect the behaviour of electroluminescence emission such as, applied voltage, applied frequency, ageing of material and types of materials. . In this paper, the EL measurement is employed to determine the effect of applied frequency on virgin LDPE at fixed and varying applied voltage. It can be observed that EL emission increases as applied frequency increases with increasing voltage applied. However, interesting EL behaviour is observed when varying frequency is applied from 10 Hz to 100 Hz.